(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Telemedicine has emerged as a transformative approach to improving access to primary health care, particularly in remote and underserved regions. By leveraging digital technologies such as video consultations, mobile health applications, and electronic health records, telemedicine enables timely medical advice, diagnosis, and continuous patient monitoring. This review examines the current evidence on telemedicine’s effectiveness in expanding primary health care access, highlighting both its benefits and challenges. Findings indicate that telemedicine can reduce geographic and economic barriers, improve patient outcomes, and enhance the efficiency of health systems. However, technological infrastructure, data security, and regulatory frameworks remain critical considerations for its widespread implementation. The study underscores the potential of telemedicine as an essential component of modern primary health care strategies.